Physical Processing of Various Forage Plants and Their Application in Aquafeed Development - Haetami, Kiki; Aisyah, Aisyah; Abun, Abun (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Feed is a crucial element in aquaculture, directly influencing the growth and reproduction of aquatic organisms. This study aims to explore the potential of forage-based ingredients as alternative feed sources to reduce reliance on costly conventional inputs such as fish meal. Various locally available forages, including aquatic plants (Azolla sp., Lemna sp., and water hyacinth), tree legumes (leucaena and calliandra), and tuber crops (cassava leaves), were evaluated based on their nutritional composition and feasibility for use in aquafeed. Processing methods such as physical (drying, grinding, pelletizing), chemical (acid and enzyme addition), and biological (fermentation using Aspergillus niger or rumen enzymes) treatments were applied to enhance digestibility and reduce antinutritional factors. Analytical assessments showed that these treatments significantly lowered crude fiber content while increasing protein concentration and improving palatability. Fermented leucaena leaves and azolla powder, for instance, demonstrated improved nutritional profiles and potential for inclusion in practical feed formulations. The study concludes that forage-based feed processing improves feed efficiency and supports sustainable, low-cost aquaculture. Continued innovation in forage processing technology is recommended to support national feed self-sufficiency goals and promote environmentally friendly aquaculture practices.